2005
DOI: 10.2144/05385st04
|View full text |Cite
|
Sign up to set email alerts
|

Housekeeping Genes in Cancer: Normalization of Array Data

Abstract: Biological maintenance of cells under variable conditions should affect gene expression of only certain genes while leaving the rest unchanged. The latter, termed "housekeeping genes," by definition must reflect no change in their expression levels during cell development, treatment, or disease state anomalies. However, deviations from this rule have been observed. Using DNA microarray technology, we report here variations in expression levels of certain housekeeping genes in prostate cancer and a colorectal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 32 publications
2
40
0
1
Order By: Relevance
“…Overall, the majority of these mRNAs are effective normalization tools, although several groups report that variability in their expression levels can exist in different sample and cell types and needs to be considered when designing a study. [1][2][3][4][5][6][7][8] For example, Vandesompele et al 9 reported that universally stable control genes do not exist, thus necessitating the development of an accurate normalization strategy for each experimental system. Aerts et al, 10 in a study of 26 tumor cell lines including prostate cancer DU-145 and PC-3, showed GAPDH has the highest variability in gene expression of commonly used controls, whereas 18s rRNA, GUS, and ACTB had the best expression stability.…”
mentioning
confidence: 99%
“…Overall, the majority of these mRNAs are effective normalization tools, although several groups report that variability in their expression levels can exist in different sample and cell types and needs to be considered when designing a study. [1][2][3][4][5][6][7][8] For example, Vandesompele et al 9 reported that universally stable control genes do not exist, thus necessitating the development of an accurate normalization strategy for each experimental system. Aerts et al, 10 in a study of 26 tumor cell lines including prostate cancer DU-145 and PC-3, showed GAPDH has the highest variability in gene expression of commonly used controls, whereas 18s rRNA, GUS, and ACTB had the best expression stability.…”
mentioning
confidence: 99%
“…This protein has been considered a housekeeping enzyme. However, it has been reported dysregulated in cancer cells [51], liver metastases [52], and in aged rats [53]. In COMT deleted mice, the changes in actin 1 might also be related to the response to stress in liver.…”
Section: Proteome Of Female Comt Knockout Livermentioning
confidence: 99%
“…An extensive literature has discussed problems related to normalization in such studies. One such problem is a change in expression of the gene/protein used for normalization-a particular concern in studies of development, differentiation, or disease (Khimani et al, 2005;Brattelid et al, 2007). Two issues in the use of arrays to assess GPCR expression are how to define the limit of detection of a receptor in terms of Δcycle-threshold [ΔC(t)] relative to the reference used for normalization, and the most appropriate statistical tests for data analysis (Khimani et al, 2005;Rubie et al, 2005).…”
Section: What Are Some Of the Problems And Limitations Of Efforts To mentioning
confidence: 99%